Effect of metabolosome encapsulation peptides on enzyme activity, coaggregation, incorporation, and bacterial microcompartment formation. Issue 5 (13th February 2020) - Juodeikis, Rokas; Lee, Matthew J.; Mayer, Matthias; Mantell, Judith; Brown, Ian R.; Verkade, Paul; Woolfson, Derek N.; Prentice, Michael B.; Frank, Stefanie; Warren, Martin J.
Abstract: Metabolosomes, catabolic bacterial microcompartments (BMCs), are proteinaceous organelles that are associated with the breakdown of metabolites such as propanediol and ethanolamine. They are composed of an outer multicomponent protein shell that encases a specific metabolic pathway. Protein cargo found within BMCs is directed by the presence of an encapsulation peptide that appears to trigger aggregation before the formation of the outer shell. We investigated the effect of three distinct encapsulation peptides on foreign cargo in a recombinant BMC system. Our data demonstrate that these peptides cause variations in enzyme activity and protein aggregation. We observed that the level of protein aggregation generally correlates with the size of metabolosomes, while in the absence of cargo BMCs self‐assemble into smaller compartments. The results agree with a flexible model for BMC formation based around the ability of the BMC shell to associate with an aggregate formed due to the interaction of encapsulation peptides. Abstract : Targeting protein cargo to bacterial microcompartments (BMCs) is reliant on the presence and effectiveness of N‐terminal encapsulation peptides. Three distinct tags were investigated for their ability to target cargo to a recombinant BMC. The three tags resulted in variations in the amount of aggregation and/or colocalization. The level of aggregation was found to influence enzymatic activity, packing, and the size and shape of the structure.